A 2DRF Pulse Sequence for Bolus Tracking in Hyperpolarized (13)C Imaging - Tang, Shuyu (Magn Reson Med, 2014)
PURPOSE: A novel application of 2D spatially-selective radiofrequency (2DRF) excitation pulses in hyperpolarized (13)C imaging is proposed for monitoring the bolus injection with highly efficient sampling of the initially polarized substrate, thus leaving more polarization available for detection of the subsequently generated metabolic products. METHODS: A 2DRF pulse was designed with a spiral trajectory and conventional clinical gradient performance. To demonstrate the ability of our 2DRF bolus tracking pulse sequence, hyperpolarized [1-(13)C]pyruvate in vivo imaging experiments were performed in normal rats, with a comparison to 1DRF excitation pulses. RESULTS: Our designed 2DRF pulse was able to rapidly and efficiently monitor the injected bolus dynamics in vivo, with an 8-fold enhanced time resolution in comparison with 1DRF in our experimental settings. When applied at the pyruvate frequency for bolus tracking, our 2DRF pulse demonstrated reduced saturation of the hyperpolarization for the substrate and metabolic products compared to a 1DRF pulse, while being immune to 0±5 ppm magnetic field inhomogeneity at 3T. CONCLUSION: 2DRF pulses in hyperpolarized (13)C imaging can be used to efficiently monitor the bolus injection with reduced hyperpolarization saturation compared to 1DRF pulses. The parameters of our design are based on clinical scanner limits, which allows for rapid translation to human studies.